THERAPEUTIC EFFECTS AND ADVERSE EVENTS OF SINGLE DOSE OF INTRAVITREAL TRIAMCINOLONE ACETONIDE INJECTION IN MACULAR EDEMA - MATHEW, BRIGHTY; SREEDHARAN, SYAM; MADHAVAN, PADMASREE KAMALA; RETNAYYAN, APARNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to study the therapeutic effects and adverse events of single dose of intravitreal triamcinolone acetonide (TA) in macular edema (ME). Methods: This prospective observational study was conducted for a period of 18 months in a tertiary care hospital. A total of 100 patients who received intravitreal injection of TA 4 mg were followed up within 1 month of injection and thereafter monthly for 3 months. Therapeutic effect was noted by improvement in visual acuity and reduction in macular thickness. Safety was assessed based on adverse events reported during the study period. The quantitative variables were analyzed by paired t-test and the qualitative variables by Wilcoxon signed-rank test and Chi-square test. Results: The mean age was 58.66±11.21 years with majority of patients (46%) in 46–60 age group. Diabetic retinopathy was the most common etiology. Fifteen patients experienced improvement in vision within 1 month, 51, 84, and 91 patients had better visual acuity after 1, 2, and 3 months, respectively, which were statistically significant (p=0.001). The mean macular thickness of 497.79±115.08 at baseline reduced to 448.62±112.48 within 1 month which further reduced to 383.72±105.79, 327.33±86.49, and 263.83±68.68 at the end of the 1st, 2nd, and 3rd months, respectively (p=0.001). The adverse events of rise in intraocular pressure, cataract, redness, pain, floaters, and subconjunctival hemorrhage were not found to be statistically significant (p>0.05). Conclusion: Intravitreal TA injection may be an effective and safe treatment option for ME due to various etiologies.